The Moderating Role of Earnings Quality in the Nexus Between Financial Risk, Profitability, Investment Opportunity Set, and Foreign Ownership with Financial Reporting Integrity - Andriyani, Amalya Diva; Yuniningsih, Yuniningsih (International Journal of Scientific Research and Management (IJSRM), 2025)
This study examines the influence of financial risk, profitability, investment opportunity set, and foreign ownership on financial reporting integrity, with earnings quality acting as a moderating variable, in Indonesian state-owned enterprises (SOEs). Using panel data from 21 SOEs listed on the Indonesia Stock Exchange from 2021 to 2024, the analysis was conducted through Partial Least Squares Structural Equation Modeling. The findings reveal that profitability significantly enhances financial reporting integrity, and this relationship is further strengthened when earnings quality is high. Meanwhile, financial risk, investment opportunity set, and foreign ownership do not show direct effects on reporting integrity. However, earnings quality weakens the influence of foreign ownership on reporting integrity and does not moderate the effects of the other variables. These results highlight the critical role of profitability and earnings quality in supporting the integrity of financial reporting within SOEs, and suggest that regulatory frameworks in these entities may mitigate risks that typically compromise reporting integrity in private firms.